Flexible Fiber Supercapacitor Using Biowaste‐Derived Porous Carbon. Issue 8 (31st July 2015) - Senthilkumar, S. T.; Selvan, R. Kalai
Abstract The front cover artwork is provided by Dr. S. T. Senthilkumar and Dr. R. Kalai Selvan, Bharathiar University (Tamil Nadu, India). The image shows the conversion of dead leaves into porous carbons and their application in a fiber supercapacitor for wearable electronics. Read the full text of the Article at 10.1002/celc.201500090.